Staging phantasmagoria : the uncanny play of live and mediatized performance : a thesis presented in partial fulfillment of the requirements for a degree of Masters in Design at Massey University - Brettell, Andrew (Massey University, 2006)
Multimedia designers working in the theatre often produce work that fails to recognize the fundamentally different spatiotemporal vocabularies of live performance and the moving image, and how they can be productively utilised to enhance theatre's inherent virtuality. This thesis argues that instead of mixing or hiding the differences between the virtual and the physical in theatre, performance design can 'play' with the two languages to produce an uncanny experience that re-establishes the strangeness of phantasmagoria' - technologies of vision that project ghostly doubles. In consumer culture, disembodied images screened by contemporary phantasmagoria such as television, cinema and the computer interface, habitually engage the spectator in a process of identification and disavowal. Integrating live performance and the mediatized image has the potential to change the spectator's response to these images. When the live performer is confronted with his or her mediatized double, the dissonance between presence and absence, materiality and immateriality, animate and inanimate is marked by disconcerting logic' and 'doubt' rather than identification and disavowal. This doubt opens up ambiguities in the spectator's preconceptions about self-identity, and particularly the belief that the phantasmatic body image is simply an immaterial copy of the body. Instead, the relationship between the body and its image becomes indeterminate and reversible, actual and virtual. Embodied research was employed to develop this hypothesis, through three site-specific performance installations. Theatre Ghosts (September, 2006, Circa Theatre). Ghost Runner [November, 2006, Wellington), and Futuna (December, 2006, Chapel of Futuna), that tested the potential dissonance between the projected image and the performing body in order to provoke uncanny spatiotemporal experiences. These experiments, presented through conceptual drawings, still and moving images, are used as vehicles to consider how the ambiguous clash between live and mediated performance suggests new ways of extending the performing body, its phantasmatic double and spaces of inhabitation.
Keywords: Performance art; Installation art; Theatre; Performance design; Performance installations